Title of report: second primary ovarian carcinomas after breast cancer diagnosis- an analysis of a single cancer centre in China - Liu, Hong; Luo, Min; Peng, Chunrong; Cheng, Xinghan; Luo, Gupo; Wang, Dengfeng; Zhang, Guonan (Frontiers in Oncology, 2025)
ObjectiveWe aimed to evaluate the clinicopathological characteristics and survival outcomes of patients with second primary ovarian carcinomas after a breast cancer diagnosis.Materials and methodsWe reviewed the medical reports of 23 patients at Sichuan Cancer Hospital between May 2002 and October 2021. We analyzed demographic and clinicopathologic characteristics, the time interval between diagnoses, and survival time. Kaplan-Meier and Cox proportional hazards regression tests were used to determine survival outcomes.ResultsThe median age of patients at the time of diagnosis of breast cancer (BC) and ovarian cancer (OC) was 46 and 49 years, respectively. Among them were 6 cases of synchronous OC and 17 instances of metachronous OC. The average interval between diagnoses of the two cancers was 62.48 months. The median OS after the second primary OC diagnosis was 38 months. According to Kaplan-Meier’s analysis, the advanced stage at presentation of BC (p=0.023) resulted in a significantly shorter interval between BC and OC diagnosis. On univariate Cox regression analysis, only BC Scarff-Bloom-Richardson (SBR) 3 Grade resulted in a considerably worse PFS (HR 0.187, p=0.048) and OS (HR 0.190, p=0.048), respectively.ConclusionWe should strengthen the follow-up management of breast cancer patients.The later the stage of breast cancer, the shorter the time interval of diagnosis of OC was. Early control of ovarian tumors and active comprehensive treatment for synchronous and metachronous breast and ovarian cancer can achieve good results.